3D simulation of machining parameters of electrochemical micromachining for stainless steel (316L). (2021) - Kumar, Abhinav; Singh, Arvind; Yadav, H.N.S.; Kumar, Manjesh; Das, Manas
Abstract: An electrochemical micromachining (EMM) removes material via anodic dissolution. Several parameters affect their machining rate as well as accuracy. Analyzing these parameters and their effects via experiments is very rigorous and time-consuming. The simulation study helps in better prediction of the parameters as well as saves time. In this paper, different parameters and their effects are analyzed during machining. A three-dimensional model is formed by making an electrolytic cell with a tungsten carbide micro-drill tool as a cathode and SS-316L as the anode surface with sodium chloride as an electrolyte. From the simulation results, it is found that on increasing the voltage and concentration of the electrolyte, material removal rate (MRR) increases. The current density decreases on increasing the interelectrode gap (IEG). A non-uniform behavior of current density is observed during EMM. The simulation results for the effect of voltage and concentration of the electrolyte over MRR is validated with the experiments. The deviation of simulation results from the experimental results is around 15%.